Religious Moderation In The Tradition Of Mahmud Village In Bandung Regency, West Java - Khalikin, Ahsanul; Reslawati; Rosidi, Achmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the religious traditions of the people of Kampung Mahmud, a Sundanese indigenous community whose social and cultural life has long been shaped by Islamic values introduced by its founder, Eyang Haji Abdul Manaf. Despite the influence of modernization, the community continues to preserve inherited traditions, particularly kasidahan arts and Islamic rituals that harmoniously integrate with Sundanese customs. At the same time, contemporary social changes, intolerance, and primordial attitudes create challenges that require strengthening the values of religious moderation and national commitment. This research focuses on the relationship between religious moderation policies and the traditions of Kampung Mahmud, the role of national commitment within local traditions, and the influence of these traditions on the religious knowledge, attitudes, and behavior of the community. The study aims to provide recommendations for the Ministry of Religious Affairs in understanding how local traditions can support the values of religious moderation while maintaining cultural identity. The findings are expected to contribute to policy development and serve as a reference for preserving indigenous traditions that remain aligned with religious and national values. This research positions Kampung Mahmud as a model of harmony between tradition, Islam, and nationality in West Java.